EFFECT OF INTRAMUSCULAR SECRETOME ON TREATMENT RESPONSE IN TYPE 2 DIABETES MELLITUS PATIENTS - DIGAMBIRO, REZA ADITYA; AMARENDRA, GERIE; HASTUTY, DEWI; ILONA, FLORINDA; CHENDRASARI, JULIAN (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2026)
Introduction: This study meant to evaluate the efficacy of intramuscular mesenchymal stem cell derived secretome therapy to improve the glycemic control among diabetic patients with Type 2 Diabetes Mellitus (T2DM) on stable insulin or oral hypoglycemic agents (OHO). n=30 per group (Insulin + Secretome; OHO + Secretome). Methods: Pre–post controlled design; biweekly 2 mL intramuscular secretome for 12 weeks; primary outcomes HbA1c, FBG, 2hPP; standard tests per normality. Participants were divided into two groups: Insulin + Secretome and OHO + Secretome. All subjects received intramuscular injections of mesenchymal stem cell (MSC)-derived secretome (2 mL) every two weeks over a 12-week period (six injections total). Primary outcomes included changes in HbA1c, fasting blood glucose (FBG), and two-hour postprandial glucose (2hPPBG). Statistical analyses used paired t-tests or Wilcoxon tests for within-group comparisons and independent t-tests or Mann-Whitney U tests for between-group comparisons. Results: At baseline, both groups had comparable HbA1c and glucose profiles. After 12 weeks, significant reductions were observed in both treatment arms. HbA1c decreased by -1.10 ± 0.45 (Insulin) and -1.33 ± 0.36 (OHO); between-group ΔHbA1c (p < 0.05). Both groups also showed clinically relevant reductions in FBG and 2hPPBG levels. No major adverse effects were reported. Conclusion: Intramuscular MSC-secretome improved glycemic control across background therapies; the benefit was modestly greater with OHO. No majoradverse events were observed